2019
DOI: 10.24326/asphc.2019.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Growth of ‘Vanda’ Maiden Sweet Cherry Trees on Three Rootstocks and After Aplication of Foliar Fertilization in a Nursery

Abstract: Cultivation of sweet cherry trees is growing in popularity in Poland thus there is an increasing demand for good quality nursery material. The growth of maiden sweet cherry trees of ‘Vanda’ depending on three rootstocks was compared within three years of the nursery experiment. Also the nutritional status as well as photosynthetic activity of maiden trees after the use of four foliar preparations were in the scope of interest. On the basis of the size of the trunk diameter and weight of maiden sweet cherry tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The maiden apple tree cultivars used in our experiment differed in their leaf contents of macro-and micronutrients. Other authors [24,25,56] also observed species-or cultivardependent differences in the effects of the same biostimulants and fertilisers on the nutrition of plants.…”
Section: The Contents Of Macro-and Micronutrients In the Leaves Of Maiden Apple Treesmentioning
confidence: 86%
See 2 more Smart Citations
“…The maiden apple tree cultivars used in our experiment differed in their leaf contents of macro-and micronutrients. Other authors [24,25,56] also observed species-or cultivardependent differences in the effects of the same biostimulants and fertilisers on the nutrition of plants.…”
Section: The Contents Of Macro-and Micronutrients In the Leaves Of Maiden Apple Treesmentioning
confidence: 86%
“…However, neither of the fertilisers (urea, calcium nitrate) used in their experiment improved the growth of the maiden apple trees significantly. In a later study [24], only one of the foliar fertilisers (Maxi Grow Excel) used in the experiment improved the growth of maiden cherry trees. Other foliar preparations and fertilisers, which also contained microelements (Black Jack and Biopuls Forte), increased the contents of nitrogen and phosphorus, and less frequently the contents of potassium, calcium, and micronutrients in the leaves of maiden sweet cherry trees.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Pol. Hortorum Cultus, 22(4), 47-66. https://doi.org/10.24326/ asphc.2023.5024 authors [Cantín et al 2010, Sitarek and Grzyb 2010, Baryła et al 2014, Świerczyński et al 2019. Baryła et al [2014] obtained 'Regina' maiden trees on the 'GiSelA 5' rootstock with a diameter of 14.2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The application of two foliar fertilisers resulted in a similar growth of the stoolings to that of the control combination. Świerczy ński et al [48] conducted an experiment that showed that only the foliar treatment of maiden sweet cherry trees with the Maxi Grow Excel fertiliser significantly improved their growth results. It is noteworthy that when the dose of mineral fertiliser is reduced, additional foliar fertilisation only compensates for the possible lack of soil nutrients but it does not improve the growth of plants.…”
Section: Growth Parameters Of Stoolingsmentioning
confidence: 99%